Analisis Keputusan Pembelian Yang Dipengaruhi Oleh Kualitas Produk dan Persepsi Harga Melalui Promosi di Midori Restaurant Bogor - Alviana Rosmasari; Yosafat Puji Hastoko (CV. ULIL ALBAB CORP, 2024)
The research aims to analyze the impact of Product Quality and Price Perception on Promotion and Purchase Decisions, both directly and indirectly in the culinary business context. A sample of 100 respondents. With research methods using questionnaires in collecting data obtained from survey results. This method uses quantitative methoes using Path Analysis. The results of this study show the direct influence of product quality, price perception and promotion variables on purchasing decision variables. The indirect influence of variable product quality and price perception affects purchase decisions through promotions.